Asuhan Keperawatan Jiwa Pada Ny. P Dengan Masalah Utama Risiko Perilaku Kekerasan Akibat Skizofrenia Paranoid Di Ruang Madrim RSJD dr. Amino Gondohutomo Provinsi Jawa Tengah - Madynatul Khuzaemah; Titi Sri Suyanti; Tati Karyawati (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Mental disorders themselves are a group of symptoms characterized by changes in a person's thoughts, feelings and behavior that cause dysfunction in carrying out daily activities. Within mental disorders there are several diagnoses, one of which is schizophrenia. Schizophrenia is a serious mental disorder characterized by decreased or inability to communicate, cognitive impairment, inability to think abstractly and experiencing difficulty in carrying out daily activities (Afeanpah et al., 2022). WHO data for 2019 shows that 1 in every 8 people or 970 million people throughout the world live with mental disorders such as anxiety disorders, depression, schizophrenia, bipolar disorder. 24 million people suffer from serious mental disorders such as schizophrenia worldwide or 1 in 300 people (0.32%) this figure is 1 in 222 people (0.45%) among adults, and 280 million people suffer from depression, including 23 million children and adolescents, 40 million people experience bipolar disorder, 301 million people experience anxiety disorders including 58 million children and adolescents (WHO, 2019).